Can We Predict Incorrect PrEP Use in High HIV Risk Situations Among Men Who Have Sex With Men? An Analysis of Be-PrEP-ared, the Belgian PrEP Demonstration Study. (1st September 2021) - Vuylsteke, Bea; Reyniers, Thijs; Nöstlinger, Christiana; Smekens, Tom; Kenyon, Chris; Laga, Marie
Abstract : Background: Pre-exposure prophylaxis (PrEP) efficacy for HIV prevention is highly correlated with the degree of adherence. The objective of this analysis was to identify PrEP users who did not correctly take their dose in high HIV exposure situations and to explore potential predictors of this behavior. Methods: Study participants completed a personal Web‐based diary during their entire follow-up, providing daily information on pill intake and sexual activity. They also completed a sociobehavioral questionnaire. The association between the number of unprotected high HIV exposure sex days (as a measure for suboptimal adherence) and potential predicting factors was examined using a logistic regression, followed by a negative binomial regression model. We also constructed a risk index score for predicting poor adherence. Results: A total of 40.8% of participants did not correctly use PrEP in at least one situation of high HIV exposure during follow-up. Not having a HIV-negative steady partner, reporting more than 10 occasional or more than 10 anonymous partners, using chemsex drugs, receiving money for sex, and a history of more than one sexually transmitted infection were significantly associated with unprotected high HIV exposure sex. The risk index score yielded a poor discriminative power (area under the curve 0.62 and 0.64). Conclusions: We observed a high proportion of suboptimal adherence. Even if none of the participants acquired HIV during the study, tailored adherence support is needed to specific men who have sex with men such as those taking chemsex drugs and those engaging in paid sex. Abstract : Supplemental Digital Content is Available in the Text.